"Shanghuo" increases disease susceptibility: Modern significance of an old TCM theory. (25th March 2020) - Pan, Ming-Hai; Zhu, Si-Rui; Duan, Wen-Jun; Ma, Xiao-Hui; Luo, Xiang; Liu, Bo; Kurihara, Hiroshi; Li, Yi-Fang; Chen, Jia-Xu; He, Rong-Rong
Abstract: Ethnopharmacological relevance: "Shanghuo", a concept based on Traditional Chinese Medicine (TCM) theory, describes a status of Yin-Yang imbalance when Yang overwhelms Yin. The imbalance of Yin-Yang resembles the breaking of homeostasis and manifests by the impaired physiological functions, which leads to the onset, recurrence, and progression of diseases. Since ancient times, Chinese Materia Medica (CMM), such as herbal tea, has been applied as a treatment for "Shanghuo". Aim of the study: This review is aimed to describe the origin of "Shanghuo" from the Yin-Yang theory in TCM, as well as explore the relevance and correlations between "Shanghuo" and diseases susceptibility from the perspective of modern medicine. We also propose several strategies from CMM to improve the status of "Shanghuo" for the purpose of treating diseases. Methods: Systematic research of articles with keywords including Shanghuo, Yin-Yang, emotional stress and disease susceptibility was done by using the literature databases (Web of Science, Google Scholar, PubMed, CNKI). Related books, PhD and master's dissertations were also researched. Full scientific plant names were validated by "The Plant List" (www.theplantlist.org ). Results: To date, a large number of publications have reported research on sub-health status, but studies about the theory or intervention of "Shanghuo" are rarely found. The articles we reviewed indicate that accumulated emotional stress is critical for the cause of "Shanghuo". As a status similar to sub-health, "Shanghuo" is also manifested by impaired physiological functions and decreased nonspecific resistance, which increase susceptibility to various diseases. What's more, some studies highlight the importance of TCM treatment towards "Shanghuo" in maintaining normal physiological functions, such as immunity, lipid metabolism and ROS clearance. Conclusions: Researches on "Shanghuo" and its mechanism are every rare currently and are in need of investigation in the future. Studies on disease susceptibility recently are mostly about susceptible genes that relate to a few parts of people, however, for most of the people, accumulated emotional stress or other stressors is accountable for the susceptibility of diseases. Given that emotional stress plays an important factor in the causation of "Shanghuo", we reviewed the articles about this relevance and discussed the connection of "Shanghuo" with disease susceptibility in a novel perspective. In addition, we have reviewed the disease susceptibility model of restraint stress from its biochemical manifestation to application in CMM assessment. Although it would be a breakthrough in evaluating CMM efficacy of attenuating disease-susceptibility, understanding the comprehensive theory and establishing more models of "Shanghuo" would be required in further investigation. Graphical abstract: Image 1